2002
DOI: 10.2298/mpns0206213b
|View full text |Cite
|
Sign up to set email alerts
|

Oral health in pregnancy

Abstract: Eating habits of pregnant women may lead to frequent snacking on candy or other decay-promoting foods, thereby increasing the risk of caries. However, very poor oral health, possible dental complications and their consequences to the health as well as emotional status represent very strong reasons for activation of dental health care in this period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…This result could be attributed to the fact that pregnant women experience several extrinsic and intrinsic changes that make them vulnerable to dental caries, such as changes in salivary production and oral microbiota, social changes influencing lifestyle, an increasingly cariogenic diet and poor brushing techniques, because of nausea and symptoms related to pregnancy. All of these factors may act as risk factors for the onset of caries. However, the precise mechanisms associated with these differences in susceptibility to dental caries according to gender are still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…This result could be attributed to the fact that pregnant women experience several extrinsic and intrinsic changes that make them vulnerable to dental caries, such as changes in salivary production and oral microbiota, social changes influencing lifestyle, an increasingly cariogenic diet and poor brushing techniques, because of nausea and symptoms related to pregnancy. All of these factors may act as risk factors for the onset of caries. However, the precise mechanisms associated with these differences in susceptibility to dental caries according to gender are still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of periodontal disease (infection of the tissues surrounding and supporting the teeth) in pregnant women is considered to be exacerbated by the increase of estrogen and progesterone concentrations. [11][12][13][14][15][16][17][18][19][20][21] It is postulated that lipopolysaccharides from the anaerobic Gram-negative periodontopathogens, stimulate the release of Background: Reports show that more than 20 million infants world-wide are born prematurely with 95% of all pre-term births occurring in developing countries. Oral colonization of Gram-negative anaerobes has been implicated as a risk factor for preterm delivery of low birth weight infants.…”
Section: Introductionmentioning
confidence: 99%
“…It is an important sign that may indicate the beginning of periodontal disease with the mother and allows the bacteria to enter the bloodstream, pass through the body and enter the placenta (2). Bleeding from the gums, according to our research, is present in 60% of pregnant women; whereas, according to research from 2002, the bleeding from the gingiva is found in 32% of pregnant women with inadequate oral hygiene findings (5). The data from 1996 indicate that periodontal disease represents a statistically significant risk factor for the premature birth and inadequate fetal body weight; in fact mothers with periodontal disease are seven times more likely to give birth prematurely or to give birth to a baby with a lower body weight (9).…”
Section: Discussionmentioning
confidence: 42%
“…Oral hygiene and its maintenance habits are important factors in the development or prevention of dental caries (5). By examining the habits of pregnant women surveyed we learned that 60% of pregnant women consume more carbohydrates during pregnancy, which is certainly a risk factor for the development of caries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation